Pendidikan Life Skill pada Pondok Pesantren dalam Menghadapi Persaingan Global - M. Syukri Afkarul Huda; Samsul Hadi (Cendekia, 2021)
Along with the times, and the tightening competition in the world of education. Many educational institutions have begun to develop several learning methods, which are so that their students can compete in the globalization competition. One of the educational institutions that has begun to implement an education system for the development of life skills is the Islamic education institution Pondok Pesantren. Pondok Pesantren is an educational institution that teaches about religion, in which there are students who live in Islamic boarding schools / dormitories. With the life skill method, it is hoped that education will develop and students / students can compete in this era of globalization. Life skills are practical guidelines that help students learn how to grow to become an individual, cooperate with others, make logical decisions, protect themselves to achieve their life goals. Keywords: Life Skill Education, Islamic Boarding School, Global Competition